EDUCATIONAL SYSTEM IN SLOVAKIA - DUCHOVICOVA, Marcela (Trends in education, 2013)
Adult Education in the Slovak Republic is an integral part of lifelong education, which has been a part and it is still a part of every Manifesto of Slovak Republic declared by its government as one of the priorities of social development. Measures to promote lifelong learning as part of several policy papers and action plans have been developed and adopted in accordance with European trends. This report deals with the issue of lifelong learning for teachers.
Keywords: engineering thinking; lifelong learning; technology.